Problems Faced by the SMDC in Improvement of the Quality of Secondary Education System - Bhattacharya, Dipak; I.P., Gowramma (JOURNAL OF INDIAN EDUCATION, 2018)
Secondary education is that stage of education which helps students to become full members of a complex modern society. It develops individual’s abilities, aptitudes, interests and qualities of character to the highest potential. The objective of the present study was to find out the issues and problems faced by the School Management and Development Committee (SMDC) in improving the quality of secondary school education system. The study was conducted on 100 SMDC members of 20 secondary schools of the sub-division of Contai (from the Purba Medinipur district of West Bengal) by using the descriptive survey method. A self-developed questionnaire for head-teachers and teachers, and interview schedule for parents were used for collection of data. Then the data were analysed by using frequency and percentage. The findings of the study show that majority of the SMDC members have opined that ineffective schooling environment and teachers’ role do not inspire dropout students to get back to schools. Close to fifty per cent of the participants viewed the lack of infrastructural facility in secondary schools as the major barrier faced by them in establishing quality education. The present study suggested that the higher authorities and local bodies should take necessary steps to remove different barriers faced by the SMDC members in improving the quality of secondary school education system.